The Role of Dental Implant in Maxillofacial Prosthetic Rehabilitation in Rizgari Teaching Hospital. - Othman A. Omar (Erbil Dental Journal)
Backgrounds and objectives: Loss of any maxillofacial subunit will certainly pose a functional, esthetic, and psychological problems. In addition, the mode of fixation of prosthesis is of major concern. This research aimed to study the role of dental implant in fixing maxillofacial prosthesis.